Modern Era Corporate Crime(s) Vis-à-vis White-Collar Crime(s): A Critical Analysis from Indian Perspective (Maharaja Surajmal Institute Law Journal, 2025)
Corporations is a conglomeration of companies which are controlled by a single organization. Nowadays, corporate frauds have risen in India. Corporations committing corporate frauds is no longer a western concept for India. India’s earlier corporate crime dates to 1958, Mundra Scam. In this paper, an attempt has been made to analysis the emerging trends of corporate crimes in India. This has been done through studying various methods of commission of corporate crimes, how the background of the offender gives impetus to commit corporate crimes, motivation behind the corporate crimes and various model of corporate frauds. Further, short comings of legislations and recommendations/suggestions to discourage corporate crimes are also discussed.
Keywords: Corporate Crime; White Collor Crime; Laws; Offender; Victim; Stake holder; Punishment; Financial Fraud